2023
DOI: 10.1039/d3dt00303e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in trivalent europium (Eu3+)-based inorganic phosphors for solid-state lighting: an overview

Abstract: Narrow band red emitting phosphors are a critical constituent, and it is still a bottleneck for the next generation smart displays and high-performance lighting (solid state lighting based white light...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 243 publications
(310 reference statements)
1
3
0
Order By: Relevance
“…The energy transfer between different Eu 3+ ions was found to be negligible, which turns out as radiative emission in the ground state of Eu 3+ . The lifetime of the LCLM:Eu 3+ phosphor is greater than that of other reported red phosphors, such as the La 2− x Eu x (MoO 4 ) 3 nanophosphor, which has a lifetime of 0.49 ms. 36 NSYM:Eu 3+ has a lifetime of 0.56 ms, 37 while that of the Li 3 BaSrY 3 (MoO 4 ) 8 :Eu 3+ phosphor is 0.457 ms. 38 Also, K 0.7 Li 0.3 Eu(WO 4 ) 2 has a lifetime of 0.426 ms. 39 Given that there is zero concentration quenching, the lifetime increased with an increase in Eu 3+ concentration in the host lattice, which is comparable with the emission intensity plot of phosphors with increasing activators. For example, the EuAlO 3 and Eu 2 O 3 stoichiometric phosphors showed a luminescence decay of ∼24 μs and ∼12 μs, respectively.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The energy transfer between different Eu 3+ ions was found to be negligible, which turns out as radiative emission in the ground state of Eu 3+ . The lifetime of the LCLM:Eu 3+ phosphor is greater than that of other reported red phosphors, such as the La 2− x Eu x (MoO 4 ) 3 nanophosphor, which has a lifetime of 0.49 ms. 36 NSYM:Eu 3+ has a lifetime of 0.56 ms, 37 while that of the Li 3 BaSrY 3 (MoO 4 ) 8 :Eu 3+ phosphor is 0.457 ms. 38 Also, K 0.7 Li 0.3 Eu(WO 4 ) 2 has a lifetime of 0.426 ms. 39 Given that there is zero concentration quenching, the lifetime increased with an increase in Eu 3+ concentration in the host lattice, which is comparable with the emission intensity plot of phosphors with increasing activators. For example, the EuAlO 3 and Eu 2 O 3 stoichiometric phosphors showed a luminescence decay of ∼24 μs and ∼12 μs, respectively.…”
Section: Resultssupporting
confidence: 59%
“…Other authors reported that the absolute QE of LiEu(MoO 4 ) 2 is 24%, K 0.7 Li 0.3 Eu(WO 4 ) 2 has an IQE of 22.48%, and SrLa 0.5 Eu 0.5 MgSbO 6 exhibits a QY of 46.5%. 39…”
Section: Resultsmentioning
confidence: 99%
“…Any degeneracy in systems with orthorhombic or lower symmetry is eliminated by the crystal field. Each of the 7 F J ( J = 1 to 6) levels can be split into up to 2 J + 1 Stark sublevels leading to a fine structure, according to the symmetry . The Eu 3+ ion would have S 4 symmetry in NaEu­(MoO 4 ) 2 , while it would have C 2 and D 2 symmetry in KEu­(MoO 4 ) 2 and RbEu­(MoO 4 ) 2 and CsEu­(MoO 4 ) 2 , respectively. , It is assumed that the splitting of the emission spectrum occurred since the symmetry of these Eu 3+ sites decreases in the order S 4 for NaEu­(MoO 4 ) 2 , D 2 for RbEu­(MoO 4 ) 2 and CsEu­(MoO 4 ) 2 , and C 2 for KEu­(MoO 4 ) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, excitation spectra of the pigment under investigation revealed two peaks, registered at 466 and 538 nm with greater separation as depicted in Figure 5(a). Emission spectra of the pigment revealed intense emission peak due to their electrons in the 4f shell, one registered at 617 nm, allocated to 5 D 0 → 7 F 2 transition and a shoulder at 595 nm due to 5 D 0 → 7 F 1 transition (Figure 5(b)) [21], which portrayed color in the red region of the visible spectrum. The energy gap connecting the triplet state of ligands and the emissive state of Eu 3+ is responsible for the sensitization of Eu 3+ ion by chromophore ligands.…”
Section: Photoluminescence (Pl) Spectra Of Pigmentmentioning
confidence: 99%